2006
DOI: 10.1016/j.bbabio.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Proton pumping in the bc1 complex: A new gating mechanism that prevents short circuits

Abstract: The Q-cycle mechanism of the bc1 complex explains how the electron transfer from ubihydroquinone (quinol, QH2) to cytochrome (cyt) c (or c2 in bacteria) is coupled to the pumping of protons across the membrane. The efficiency of proton pumping depends on the effectiveness of the bifurcated reaction at the Q(o)-site of the complex. This directs the two electrons from QH2 down two different pathways, one to the high potential chain for delivery to an electron acceptor, and the other across the membrane through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
146
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(158 citation statements)
references
References 86 publications
10
146
2
Order By: Relevance
“…Induced curvature profiles are known to exert a segregating force between different types of proteins in the membrane (Frese et al, 2008). stoichiometry is 3:1 (Cartron et al, 2014), consistent with earlier observations (Crofts, 2004;Crofts et al, 2006), corresponding to approximately 4 cytbc 1 dimeric complexes per vesicle. Chromatophore vesicles typically contain 1-2 ATP synthases (Feniouk et al, 2002;Cartron et al, 2014).…”
Section: Supramolecular Organization Of a Chromatophore Vesicle Adaptsupporting
confidence: 87%
See 1 more Smart Citation
“…Induced curvature profiles are known to exert a segregating force between different types of proteins in the membrane (Frese et al, 2008). stoichiometry is 3:1 (Cartron et al, 2014), consistent with earlier observations (Crofts, 2004;Crofts et al, 2006), corresponding to approximately 4 cytbc 1 dimeric complexes per vesicle. Chromatophore vesicles typically contain 1-2 ATP synthases (Feniouk et al, 2002;Cartron et al, 2014).…”
Section: Supramolecular Organization Of a Chromatophore Vesicle Adaptsupporting
confidence: 87%
“…The primary components of chromatophore vesicles in purple bacteria, as depicted in Figure 1, are, in order of energy utililization (Cogdell et al, 2006,Cartron et al, 2014: (i) light harvesting complex 2 (LH2) (Koepke et al, 1996;Papiz et al, 2003); (ii) light harvesting complex 1 (LH1 Sener et al, 2009]); (iii) RC (Jamieson et al, 2002;Strümpfer and Schulten, 2012a); (iv) cytbc 1 (Crofts, 2004;Crofts et al, 2006); and (v) ATP synthase (Feniouk and Junge, 2009;Hakobyan et al, 2012). RC-LH1 complexes typically form dimeric RC-LH1-PufX complexes facilitated by the polypeptide PufX Sener et al, 2009), although monomeric complexes are also found in membranes from photosynthetically grown cells at a ratio of approximately 10% .…”
Section: Supramolecular Organization Of a Chromatophore Vesicle Adaptmentioning
confidence: 99%
“…In some models the SQ is thermodynamically stabilized (45), thus lowering its reactivity with O 2 ; in other models it is specifically destabilized (3,36), limiting its reactivity with O 2 by lowering its steady-state concentration. Some models posit that the SQ is shielded from O 2 within the Q o site (3), while access to the site or its reactivity is proposed to be allosterically (46,47) or electrostatically (14,27) gated. Still, other models deny the existence of an SQ intermediate altogether (21).…”
Section: Discussionmentioning
confidence: 99%
“…The key question in cyt bc complexes is how the Q o site minimizes bypass reactions while maintaining high flux through the Q-cycle (14,27,28). The question is profound because the bypass reactions are vastly more thermodynamically favored (21,29).…”
mentioning
confidence: 99%
“…The chemistry of oxygen reduction by cytochrome c oxidase is used to gate proton channels and alter proton affinities resulting in proton pumping, but conformational changes must be subtle compared to either Complex I or the ATP synthase [61]. Complex III has a unique ''Q-cycle'' to move charges across the membrane and a large conformational change of the Rieske Fe-S subunit to assure the two electrons from quinol are bifurcated, i.e., directed to different electron acceptors [62]. The enzymology of each of these systems is distinct from the others and each is a remarkable testament to the different ways that evolution has solved the problem of both generating and utilizing the proton motive force across a biological membrane.…”
Section: The Different Mechanisms Of Coupling To the Proton Electrochmentioning
confidence: 99%